Employment Components and Ecosystem on Working Poor in an Emerging Economy - Ngah, Rohana; Abdurakhmanova, Gulnora K.; Fayzieva, Muyassarzoda K.; Kurbonov, Samandar P.; Goyipnazarov, Sanjar B.; Irmatova, Aziza; Sunnat kizi, Amirdjanova Sitora; Rakhmatullayeva, Shakhnoza (Ital Publication, 2025)
As an emerging economy, Uzbekistan is progressing rapidly in economic growth. The progress caused the rising number of working poor and poverty rate. Only a few studies focus on the impact on the working poor, especially in emerging economies. Employment components and ecosystems are critical to ensure a sustainable economy, stability, and growth. Information relating to the working poor is limited, and how the working poor navigate through challenges in employment is still unknown. The objective of the study is to explore the impact of employment and the ecosystem on the working poor in Uzbekistan. A quantitative approach was conducted through a face-to-face survey in fourteen states using simple random sampling. Data collected from 3298 respondents was then analyzed through descriptive analysis and multiple regression to investigate the relationship between variables. The findings revealed that employment components like opportunity, retraining, and income fairness are crucial to the working poor, as well as social infrastructure, taxes, and union support. This study contributes to the literature relating to poverty. The study also offers practical insights into how employment matters relating to the working poor, empowering policymakers and researchers to make informed decisions.